The Intestinal Microbiome Predicts Weight Loss on a Calorie-Restricted Diet and Is Associated With Improved Hepatic Steatosis - Dong, Tien S.; Luu, Kayti; Lagishetty, Venu; Sedighian, Farzaneh; Woo, Shih-Lung; Dreskin, Benjamin W.; Katzka, William; Chang, Candace; Zhou, Yi; Arias-Jayo, Nerea; Yang, Julianne; Ahdoot, Aaron I.; et al. (Frontiers in Nutrition, 2021)
Background: The microbiome has been shown in pre-clinical and epidemiological studies to be important in both the development and treatment of obesity and metabolic associated fatty liver disease (MAFLD). However, few studies have examined the role of the microbiome in the clinical response to calorie restriction. To explore this area, we performed a prospective study examining the association of the intestinal microbiome with weight loss and change in hepatic steatosis on a calorie-restricted diet. Methods: A prospective dietary intervention study of 80 overweight and obese participants was performed at the Greater West Los Angeles Veterans Affair Hospital. Patients were placed on a macronutrient standardized diet for 16 weeks, including 14 weeks of calorie restriction (500 calorie deficit). Body composition analysis by impedance, plasma lipid measurements, and ultrasound elastography to measure hepatic steatosis were performed at baseline and week 16. Intestinal microbiome composition was assessed using 16S rRNA gene sequencing. A per protocol analysis was performed on all subjects completing the trial (n = 46). Results: Study completers showed significant reduction in weight, body mass index, total cholesterol, low density lipoprotein, and triglyceride. Subjects who lost at least 5% of their body weight had significantly greater reduction in serum triglyceride and hepatic steatosis than those with <5% body weight loss. Enterococcus and Klebsiella were reduced at the end of the trial while Coprococcus and Collinsella were increased. There were also significant baseline microbiome differences between patients who had at least 5% weight loss as compared to those that did not. Lachnoclostridium was positively associated with hepatic steatosis and Actinomyces was positively associated with hepatic steatosis and weight. Baseline microbiome profiles were able to predict which patients lost at least 5% of their body weight with an AUROC of 0.80. Conclusion: Calorie restriction alters the intestinal microbiome and improves hepatic steatosis in those who experience significant weight loss. Baseline microbiome differences predict weight loss on a calorie–restricted diet and are associated with improvement in hepatic steatosis, suggesting a role of the gut microbiome in mediating the clinical response to calorie restriction.